Dinamika Kualitas Audit: Auditor Characteristics dan PCAOB Inspections - Sepky Mardian (Agregat: Jurnal Ekonomi dan Bisnis, 2017)
This study aimed to find the effects of auditor characteristics on audit quality. Audit characteristic measured by auditor licences, gender, age and audit firm affiliation. While the audit quality proxied by auditor violations conducted by auditor and identified by PCAOB. The data collected from PCAOB Settled Disciplinary listed by PCAOB in its website. Logistic regression is used to test the hypothesis. The study found that all variables did not effect the auditor characteristics on audit quality.